Musicians and their work: gender and race differences - Segnini, Liliana Rolfsen Petrilli (Tempo Social, 2014)
Consubstantial social relations of class, gender and race/skin colour inform differences in the ways in which musicians experience the artistic field, whether they are engaged in long-term or intermittent work. Statistical data shows that the music field is predominantly composed of white males (48% of the total). Class relations determined by socioeconomic background also prove important in terms of professional training and work, especially that of soloists, among whom we can again observe the predominance of white males.